Beban Kerja Unit Pelaksana Teknis Badan Pemadam Kebakaran Kabupaten Bungo untuk Pelayanan Masyarakat - POIRAN - POIRAN (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2019)
This article aims to find out the workload given to the firefighting UPTD in Bungo district, using a descriptive method and a qualitative approach. Data collection techniques used were interviews with informants set at 15 (fifteen) people consisting of: Head of Agency; Secretary of the Agency; Head of Prevention and Preparedness Division; Head of Emergency and Logistics; Head of UPTB; 2 (two) UPTB Staff; 5 (five) Danru people; 3 (three) people. Research results The workload of the Bungo District Fire Extinguisher Technical Implementation Unit on service to the community is: The number of Bungo Regency firefighters in 2018 was 378 people who dispersed at 8 (eight) fire stations called the Fire Management Region (WMK). Of the 378 Damkar task forces there were 281 people who had attended education and training and had certificates according to qualification standards. The performance of the Bungo District Government in providing Damkar apparatus that has certification according to the qualification standards has only reached 74.33%, while the achievement target of SPM up to 2015 is 85%. There is a gap of 85% - 74.33% = 10.67%. Then the gap is 10.67%. the SPM target must be met in the preparation of development planning and calculation of regional budgets